Worker Management and the Modern Industrial Enterprise: A Reply - Atkinson, A. B. (Quarterly Journal of Economics, 1975)
Journal Article Worker Management and the Modern Industrial Enterprise: A Reply Get access A. B. Atkinson A. B. Atkinson University of Essex Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 89, Issue 4, November 1975, Pages 670–672, https://doi.org/10.2307/1884703 Published: 01 November 1975